Proses Adaptasi Masyarakat terhadap Kebudayaan Kampung Adat Kuta - Wulan Permatasari; Vicky Agus Arwanda; Adhesa Bagus Putrama Suminar (Jurnal Hukum, Administrasi Publik dan Negara, 2024)
This study investigates the adaptation process carried out by the Kuta Traditional Village community towards their culture amidst the dynamics of modernization. Kuta Traditional Village is a cultural entity rich in traditions and noble values, but faces significant challenges in maintaining its identity in the contemporary era. This research explores how the Kuta Traditional Village community interacts with social, economic and technological changes that change their lifestyle, while still maintaining their unique cultural heritage. Qualitative methods are used to explore the dynamics of this adaptation, providing insight into the strategies and responses they apply in facing changing times.